Bridging research and policy: Advancing the Nepal Public Policy Review’s role in policy-relevant scholarship - Khadka, Deepak (Nepal Public Policy Review, 2025)
The Nepal Public Policy Review was launched as a multidisciplinary journal to provide an academic platform for research relevant to public policy. It has published three volumes, including a special issue arising from a symposium. Following a critical review of the journal’s policies, we identified the need for better alignment between academic research and public policy. In response, we redefined the journal’s purpose to bridge research with policy, updating the Aims and Scope to encourage collaboration between researchers and the policy community. This shift emphasizes the importance of clear and accessible communication for policymakers. To facilitate this, we introduced new manuscript requirements, including sections for Policy Recommendations and Suggested Course of Action to translate research findings into actionable policy steps. We also introduced an initial formative editorial assessment for manuscripts before peer review. This aimed to enrich the research and ensure its alignment with relevant policies. Piloted in Volume 4, the manuscript improvement initiative successfully enhanced five articles by translating their conclusions into detailed policy recommendations. Positive feedback from authors and reviewers affirmed the success of this approach. We consider the manuscript improvement a success and will expand it in future volumes, along with exploring broader mentoring for both academics and policy professionals.